Plastidic ACCase Ile-1781-Leu is present in pinoxaden-resistant southern crabgrass (Digitaria ciliaris). Issue 1 (November 2019) - Basak, Suma; McElroy, J. Scott; Brown, Austin M.; Gonçalves, Clebson G.; Patel, Jinesh D.; McCullough, Patrick E.
Abstract: Southern crabgrass [ Digitaria ciliaris (Retz.) Koeler] is an annual grass weed that commonly infests turfgrass, roadsides, wastelands, and cropping systems throughout the southeastern United States. Two biotypes of D. ciliaris (R1 and R2) with known resistance to cyclohexanediones (DIMs) and aryloxyphenoxypropionates (FOPs) previously collected from sod production fields in Georgia were compared with a separate susceptible biotype (S) collected from Alabama for the responses to pinoxaden and to explore the possible mechanisms of resistance. Increasing rates of pinoxaden (0.1 to 23.5 kg ha −1 ) were evaluated for control of R1, R2, and S. The resistant biotypes, R1 and R2, were resistant to pinoxaden relative to S. The S biotype was completely controlled at rates of 11.8 and 23.5 kg ha −1, resulting in no aboveground biomass at 14 d after treatment. Pinoxaden rates at which tiller length and aboveground biomass would be reduced 50% (I50 ) and 90% (I90 ) for R1, R2, and S ranged from 7.2 to 13.2 kg ha −1, 6.9 to 8.6 kg ha −1, and 0.7 to 2.1 kg ha −1, respectively, for tiller length, and 7.7 to 10.2 kg ha −1, 7.2 to 7.9 kg ha −1, and 1.6 to 2.3 kg ha −1, respectively, for aboveground biomass. Prior selection pressure from DIM and FOP herbicides could result in the evolution of D. ciliaris cross-resistance to pinoxaden herbicides. Amplification of the carboxyl-transferase domain of the plastidic ACCase by standard PCR identified a point mutation resulting in an Ile-1781-Leu amino acid substitution only for the resistant biotype, R1. Further cloning of PCR product surrounding the 1781 region yielded two distinct ACCase gene sequences, Ile-1781 and Leu-1781. The amino acid substitution, Ile-1781-Leu in both resistant biotypes (R1 and R2), however, was revealed by next-generation sequencing of RNA using Illumina platform. A point mutation in the Ile-1781 codon leading to herbicide insensitivity in the ACCase enzyme has been previously reported in other grass species. Our research confirms that the Ile-1781-Leu substitution is present in pinoxaden-resistant D. ciliaris .